Vulnerable Neotropical migratory songbird demonstrates flexibility in space use in response to rainfall change. Issue 2 (25th February 2022) - Brunner, Alicia R; Marra, Peter P; Tonra, Christopher M
Abstract: Behavioral flexibility of individuals is essential if organisms are to ultimately adapt to climate change. As environmental conditions, such as precipitation patterns become increasingly variable, fine-scale spatiotemporal flexibility in space use may allow for individuals to track resources during periods of adverse or atypical conditions. Individual behavioral flexibility is observable over short timeframes and can therefore be used to assess resilience of a species to projected shifts in climate. The goal of our study was to determine if and how individuals modified their space and habitat use in response to rainfall-driven changes in resources throughout a period of atypical seasonal rainfall patterns. We used radio telemetry to estimate home ranges of nonbreeding Swainson's Warblers ( Limnothlypis swainsonii ) in 2 time frames (bi-seasonally and bi-weekly) in Jamaica during dry and wet periods. We measured habitat structure and food (leaf litter arthropod) availability within each home range to determine possible predictors of space use change. Individuals modified the area and/or location of their home ranges with changes in precipitation, and those occupying more open habitats had greater changes in home range area as seasonal rainfall increased. As food increased following rain, individuals constricted their home ranges (bi-weekly) or shifted spatially (bi-seasonally) to a novel area with greater food availability. This suggests individuals are able to rapidly respond to how their environment changes, presumably adjusting to trade-offs between home range size and resource availability. This flexibility may be a key behavioral component in enduring long-term increasingly unpredictable environmental variability and may have population-level consequences. These responses are, however, mediated by habitat, suggesting the ability to respond to variable or poor conditions is not homogeneous across a population. Lay Summary: Neotropical migratory birds wintering in the Caribbean are experiencing variable rainfall patterns both between and within nonbreeding seasons. Temporal flexibility in space use may allow for individuals to better track resources during periods of adverse or atypical rainfall conditions. We tracked the home ranges of nonbreeding Swainson's Warblers ( Limnothlypis swainsonii ) at 2 time scales (bi-seasonally and bi-weekly) in Jamaica during both dry and wet periods to determine how space use differed with varying environmental characteristics, food and habitat structure. As food increased following rain, individuals used smaller areas, moved to areas with higher food abundance, and overall, birds that occupied lower quality open habitats changed their use of space the most. Individuals are responding to environmental change during the nonbreeding season, and such flexibility may be crucial for populations to endure rapid increases in environmental variability. Graphical Abstract: